Analisis Determinan Persaingan Industri Telekomunikasi (PT. Indosat Ooredoo, PT. Telkomsel, PT. XL Axiata) di Indonesia Dalam Pasar Oligopoli - Milla Naeruz (Quantitative Economics Journal, 2018)
Nowadays, cellular phones are highly needed and become the necessities of life. The formulation of the problem was whether the factors of price/tariff, promotion, the number of customers, the number of employees, and tower networks influenced the competition (income) in telecommunication in Indonesia. The theory used in the research was the theory of micro economy and management which were related to income, competition, employees, price, and customers. Secondary data were analyzed quantitatively in the numerical form and time series by using multiple regression models. They were gathered from books, journals, research results, and other sources which were relevant to this research. Dependent variable was competition (income of telecommunication industry), while mindependent variables were tariff/price, the number of customers, the number of employees, promotion, and network. The result and the conclusion of the research showed that the number of customers and tariff had the most dominant influence on competition, while employees, promotion, and network/bts had insignificant influence on competition even though these three variables were the facility to increase company’s income. Therefore, the management of the company should be careful in identifying competitors and in making policies.